Relacje między wyborem estetycznym a politycznym w performansach parapolitycznych, politycznych i metapolitycznych - Kocemba, Joanna (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2017)
In this paper, the author reflects on the relationship between the aesthetic and political choice in performance. The considerations are based on the examples of Janusz Palikot’s rally, Critical Mass, Pobyt tolerowany and Portfolio (by Ewa Łukasiewicz, Weronika Fibich), O miłości (by Julia Jakubowska, Paweł Korbus), Mandala (by Iza Giczewska). Assuming that each performance is political because it’s oriented towards the viewer the performances were divided as: quasi-political, political and metapolitical. Using the tools from “Transformative Power of Performance: A New Aesthetics” by Erika Fischer-Lichte the performances were analysed and assessed depending on whether their materiality was formed as a result of an aesthetic choice or as a result of political choice. Among the conclusions we can find the statement that the more politics in the performance, the more aesthetic choices are equal to the political choices.In this paper, the author reflects on the relationship between theaesthetic and political choice in performance. The considerationsare based on the examples of Janusz Palikot’s rally, Critical Mass,Pobyt tolerowany and Portfolio (by Ewa Łukasiewicz, WeronikaFibich), O miłości (by Julia Jakubowska, Paweł Korbus), Mandala(by Iza Giczewska). Assuming that each performance is political becauseit’s oriented towards the viewer the performances were dividedas: quasi-political, political and metapolitical. Using the tools from“Transformative Power of Performance: A New Aesthetics” by ErikaFischer-Lichte the performances were analysed and assessed dependingon whether their materiality was formed as a result of an aestheticchoice or as a result of political choice. Among the conclusions we canfind the statement that the more politics in the performance, the moreaesthetic choices are equal to the political choices..